Competitiveness regulation of dairy products production in the Crimea - Volodkina A. A. (Interactive science, 2016)
the article outlines the results of studying the major problems concerning supporting competitiveness and quality of dairy products in the Crimea. The researchers compared the level of competitiveness of the dairy enterprise ltd. «Бег» with other brands of milk and suggested measures to improve the efficiency and effectiveness of competitiveness management of dairy products in this region.
Keywords: качество; конкурентоспособность; потребитель; эффективность; метод экспертных оценок; управление конкурентоспособностью; quality; effectiveness; efficiency; competitiveness; молочная продукция; competitiveness management; dairy products; consumer; expert evaluation method